Volver al Paraíso: Eva en los siglos XX y XXI. Reescrituras femeninas del mito de Adán y Eva - Carbajosa Pérez, Mónica (2023)
Several studies on anthropogonic myths and on the origins of patriarchy agree in pointing out that the myth of Adam and Eve is one of the most influential in shaping the identity and destiny of women in Western civilization. This paper analyzes a corpus of literary works from the 20th and 21st century written by Spanish and Latin American women writers that offer a female vision of the myth. By transferring the voice to Eve, they rewrite the plot and redefine the characters. The article focuses on the analysis of two of the modifications that these works, manifestly hypertextual, introduce with respect to the hypotext: Eve’s perspective and voice, and the transformation of the story of the creation of the primordial couple.